Efektivitas Metode Jarimatika dengan Model PBL terhadap Kemampuan Berhitung Perkalian pada Siswa Kelas 3 SD - Alufiyah Azmi; R. Firman Nurbudi Prijambodo; Nisfil Maghfiroh Meita (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study was conducted because some students are still less able in learning multiplication or have not memorized multiplication from 1 to 10 and students who still think that multiplication operations are difficult to memorize, so that their multiplication calculation ability is still quite low. This study aims to determine the effectiveness of the jarimatika method with the Problem Based Learning (PBL) model on the multiplication calculation ability of grade 3 students of SD Negeri Pangarangan V. This study uses a quantitative descriptive research type with a descriptive model and a pre-experimental design approach. The sample in this study used 30 grade 3 students. Data collection techniques used in this study were observation, interviews, documentation and tests. Hypothesis testing requires data collection, in this study the researcher used a test (pretest-posttest). The implementation of the pretest and posttest can be seen from the average. The average pretest score obtained by students was 60.33 and the posttest score obtained by students was 80.00. Furthermore, the prerequisite test, namely the normality test, the researcher used the Shapiro Wilk technique. Based on the results of the normality test, the P-value at Sig. (2-tailed) in the pretest is 0.062 <0.05 and the P-value at Sig. (2-tailed) in the posttest is 0.065 <0.05. Next is the hypothesis test using the t-test (paired sample t-test), the results of the t-test calculation (paired sample t-test) using the help of SPSS 26 computer software show the P-value results at Sig. (2-tailed) of 0.000 which means <0.05 means H0 is rejected and Ha is accepted. Thus, the results of the hypothesis test state that the jarimatika method with the Problem Based Learning (PBL) model is effective for the multiplication calculation ability of grade 3 students at SDN Pangarangan V.